Intrathecal administration of colistin for meningitis due to New Delhi metallo-β-lactamase 1(NDM-1)-producing Klebsiella pneumoniae. Issue 3 (March 2016) - Inamasu, Joji; Ishikawa, Kiyohito; Oheda, Motoki; Nakae, Shunsuke; Hirose, Yuichi; Yoshida, Shunji
Abstract: Infection by bacteria carrying New Delhi metallo-β-lactamase 1 (NDM-1) is becoming a global health problem. We report a case of meningitis caused by NDM-1-producing Klebsiella pneumoniae, for which intrathecal administration of colistin was curative. A previously healthy 38-year-old Japanese man, who lived in Hyderabad, India, suddenly collapsed and was brought to a local hospital. He was diagnosed with subarachnoid hemorrhage and underwent emergency surgery which included partial skull removal. Approximately 1 month after surgery, he was repatriated to Japan and was admitted to our institution with information that he had been treated for multi-drug resistant Acinetobacter infection with colistin. A week after admission, he developed aspiration pneumonia due to NDM-1-producing K. pneumoniae, which was successfully treated by intravenous (IV) administration of colistin. Subsequently, he underwent a surgical procedure to repair his skull defect. He developed high-grade fever and altered mental status on postoperative day 2. NDM-1-producing K. pneumoniae was identified in the cerebrospinal fluid, establishing the diagnosis of meningitis. Although IV colistin was only partially effective, intrathecal colistin (10 mg daily by lumbar puncture for 14 days) successfully eradicated the meningitis. Because of economic globalization, NDM-1-producing bacteria may be brought to Japan by those who are repatriated after sustaining critical illnesses and being treated in foreign countries. This report may provide useful information on the treatment of central nervous system infection by NDM-1-producing bacteria.